2001
DOI: 10.1038/sj.cgt.7700347
|View full text |Cite
|
Sign up to set email alerts
|

The immune anti-tumor effects of GM-CSF and B7-1 gene transfection are enhanced by surgical debulking of tumor

Abstract: Malignant mesothelioma ( MM ) is a solid tumor largely unresponsive to conventional therapies. Immunological gene therapy shows promise in murine models and human clinical trials; however, the role of surgery in combination with gene therapy has not been widely studied. The aim of this study was to determine if debulking surgery improved the effectiveness of gene therapy in a murine MM model. Mice were subcutaneously inoculated with the MM cell line, AC29, at two different sites, 4 days apart, to allow a surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 39 publications
3
19
1
Order By: Relevance
“…challenge with wild-type tumor cells than the vaccine expressing either molecule alone (38). On the other hand, some studies reported that such combinations had no synergistic or enhanced antitumor effects on melanoma, squamous cell cancer, or malignant mesothelioma models (19,36,37). Collectively, all of these reports show that the antitumor effects of combining GM-CSF and B7.1 were either enhanced or kept the same as single gene therapy; yet, our results showed the opposite.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…challenge with wild-type tumor cells than the vaccine expressing either molecule alone (38). On the other hand, some studies reported that such combinations had no synergistic or enhanced antitumor effects on melanoma, squamous cell cancer, or malignant mesothelioma models (19,36,37). Collectively, all of these reports show that the antitumor effects of combining GM-CSF and B7.1 were either enhanced or kept the same as single gene therapy; yet, our results showed the opposite.…”
Section: Discussioncontrasting
confidence: 39%
“…Previous studies attributed the lack of enhanced antitumor effects by GM-CSF and B7.1 combination therapies to the following reasons: (a) inhibitory activity of these immune factors with each other, (b) dosage of inoculated tumor cells, (c) low immunogenicity of tumor cells, and (d) absence of MHC on tumor cells (19,37). All these factors might contribute to the reduced antitumor effects of the GM-B7.1/RT-2 tumor vaccine observed in our tumor model.…”
Section: Discussionmentioning
confidence: 99%
“…68 In preclinical studies, this recombinant showed enhanced efficacy in combination with debulking surgery, chemotherapy (gemcitabin and cisplatin), or cyclooxygenase-2 inhibition. 1,71,72 A similar synergy was seen when GM-CSF or B7.1 gene therapy was combined with debulking surgery 67 or when IFN-a treatment was combined with chemotherapy. 73 The fact that IFN-a and -b stimulate crosspriming of CD8 þ T cells, 74 suggests that this immune priming step may be rate-limiting in the efficacy of conventional treatments.…”
Section: 27mentioning
confidence: 93%
“…Target cells were labeled with 51 Cr by incubating 3 ϫ 10 cells in a 6-well plate with 3.7 MBq of 51 Cr (New England Nuclear, Wellesley, MA) in culture medium for 18 hr and were then washed 3 times with PBS. Varying numbers of effector cells were mixed with target cells to yield E:T ratios of 60:1 to 7.5:1.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%